2021
DOI: 10.18433/jpps31877
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of albumin nanoparticles for the delivery of a novel β-tubulin polymerization inhibitor

Abstract: Purpose: The ultimate goal of this study is to develop a novel delivery system for a new potent cytotoxic compound, CCI-001, with anti-b tubulin activity, so that the drug can be effectively administered and at the same time its harmful side effects can be reduced. Methods: In the current study, CCI-001 was loaded into serum albumin (SA), using a modified desolvation method, generating CCI-001-SA nanoparticles. Both bovine and human SA were used for the encapsulation of this drug candidate. Optimum conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“… 68 Based on the literature study ( Table 2 ), six studies discussed optimization by varying the ratio of drug: BSA. According to Abd Ellah et al 69 Jenita, Wilson, and Chocalingam, 70 Spada et al 71 Jenita, 72 and Syed and Sailaja 73 the particle size and polydispersity index value increase with the amount of BSA used. This is in accordance with previous studies also stating that the higher the concentration of BSA, the larger the particle size and the greater the polydispersity index.…”
Section: Methodsmentioning
confidence: 98%
“… 68 Based on the literature study ( Table 2 ), six studies discussed optimization by varying the ratio of drug: BSA. According to Abd Ellah et al 69 Jenita, Wilson, and Chocalingam, 70 Spada et al 71 Jenita, 72 and Syed and Sailaja 73 the particle size and polydispersity index value increase with the amount of BSA used. This is in accordance with previous studies also stating that the higher the concentration of BSA, the larger the particle size and the greater the polydispersity index.…”
Section: Methodsmentioning
confidence: 98%
“… Challenges in clinical trials using colchicine. In the year 2009, the US FDA granted approval for the use of colchicine in the treatment of familial Mediterranean fever (FMF) and the prevention and management of gout attacks ( 41 ). Detailed investigations into the mechanisms of action have revealed that colchicine exhibits its effects by binding to microtubules, thereby exerting an influence on numerous cellular processes ( 42 ).…”
Section: Challenges In Cardiovascular Endeavormentioning
confidence: 99%
“…It has been indicated that nano-based compounds are highly successful among anticancer drugs to potentially interact with tubulin. So far, it has been shown that many different inorganic NPs or nanocarriers have the ability to interact with MTs or carry tubulin polymerization inhibitors [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%